Homological approach to problems with jumping non-linearity. (October 2016) - Maalaoui, Ali; Martino, Vittorio
Abstract: In this paper, we use a perturbed version of the Rabinowitz–Floer homology to find solutions to PDE's with jumping nonlinearities. As applications, we find branches for the Fucik spectrum for the Laplace equation and for systems on manifolds that fiber over S 1 .